SATRIYA Government Culture, Achievement Motivation, and Its Impact on the Performance of Civil Servants in Kulon Progo Regency Government - Antonia Eka Sari Widyastuti (POPULIKA, 2025)
This study analyzes the relation of implementing SATRIYA as an organizational culture and achievement motivation on the performance of civil servants in Kulon Progo Regency government. The results of this study are expected to provide recommendations for the government regarding follow-up actions on the implementation of organization culture policies. The results of this study can serve as a reference for other regional governments to improve public service quality and bureaucratic performance through the implementation of work culture based on local wisdom. Using a quantitative method and statistical analysis, data collection was carried out by questionnaire instrument with the results showing that all statement items were valid and had a very high level of reliability. The research sample was selected using a saturated sampling technique consisting of civil servants in Kulon Progo Regency, including the Department of Culture, the Library and Archives Department, the Regional Disaster Management Agency, the Investment and Integrated Services Agency, the Regional Financial and Asset Agency, and the Population and Civil Registry Office, with a total of 150 respondents. The research findings indicate that the SATRIYA Government Culture and achievement motivation partially have a positive and significant impact on the performance of civil servants within the Kulon Progo Regency government. Simultaneously, the SATRIYA Government Culture and achievement motivation variables contribute 71.2% to the improvement of civil servant performance, while the remaining 28.8% is influenced by other variables not examined in this study. Keywords: Achievement Motivation, Organizational Culture, Performance, SATRIYA.